2018
DOI: 10.1038/s41467-017-02722-7
|View full text |Cite
|
Sign up to set email alerts
|

Similar neural responses predict friendship

Abstract: Human social networks are overwhelmingly homophilous: individuals tend to befriend others who are similar to them in terms of a range of physical attributes (e.g., age, gender). Do similarities among friends reflect deeper similarities in how we perceive, interpret, and respond to the world? To test whether friendship, and more generally, social network proximity, is associated with increased similarity of real-time mental responding, we used functional magnetic resonance imaging to scan subjects' brains durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
244
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(264 citation statements)
references
References 53 publications
14
244
3
3
Order By: Relevance
“…Based on these intrasubject and intersubject features of rsFC, we hypothesized that subjects with similar psychiatric states may have similar connectome patterns; and inversely, their common connectome features (termed as g roup‐specific functional connectome [GFC]) (Gratton et al, ) may help in discriminating whether an unknown individual has a similar psychiatric state to that of the cohort study. In support of this hypothesis, Parkinson, Kleinbaum, and Wheatley () found that the similarity of neural responses to audiovisual movies decreased with increasing distance between individuals in their shared social network.…”
Section: Introductionmentioning
confidence: 92%
“…Based on these intrasubject and intersubject features of rsFC, we hypothesized that subjects with similar psychiatric states may have similar connectome patterns; and inversely, their common connectome features (termed as g roup‐specific functional connectome [GFC]) (Gratton et al, ) may help in discriminating whether an unknown individual has a similar psychiatric state to that of the cohort study. In support of this hypothesis, Parkinson, Kleinbaum, and Wheatley () found that the similarity of neural responses to audiovisual movies decreased with increasing distance between individuals in their shared social network.…”
Section: Introductionmentioning
confidence: 92%
“…In other recent research Parkinson, Kleinbaum, and Wheatley () used intersubject correlation analysis (Hasson, Nir, Levy, Fuhrmann, & Malach, ) to assess similarity in the brain activation between pairs of individuals while participants naturally watch movies. Results demonstrated that the distance between pairs in the overall social network could be accurately predicted based on the similarity in activation across multiple areas of cortex, between friendship pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Social and emotional closeness, sympathy, bonding/friendship of humans are emergent self-similar aspects of shared subject Senomes , as seen for example in similar neural responses to sensory stimulation [49,100103]. All this suggests that a shared species specific Senome , as collective information and communication, underlies social networks in humans [100,101].…”
Section: Implications Of the Cellular Senome For Multicellularity Andmentioning
confidence: 99%
“…Social and emotional closeness, sympathy, bonding/friendship of humans are emergent self-similar aspects of shared subject Senomes , as seen for example in similar neural responses to sensory stimulation [49,100103]. All this suggests that a shared species specific Senome , as collective information and communication, underlies social networks in humans [100,101]. Therefore, it is argued that the Senome has direct pertinence for understanding human perception and understanding of mental signals from outside (memes) or from within our own bodies (perceived as emotions and feelings) and further relevances for both individual and social cognition [100107], that ultimately leads to the theory of mind [5,106,108,109] and human cultural evolution [110113].…”
Section: Implications Of the Cellular Senome For Multicellularity Andmentioning
confidence: 99%